Modern Solutions for Ancient Pathogens: Direct Pathogen Sequencing for Diagnosis of Lepromatous Leprosy and Cerebral Coenurosis. (23rd August 2022) - Young, Bernadette C; Bush, Stephen J; Lipworth, Sam; George, Sophie; Dingle, Kate E; Sanderson, Nick; Brankin, Alice; Walker, Timothy; Sharma, Srilakshmi; Leong, James; Plaha, Puneet; Hofer, Monika; et al.
Abstract: Microbes unculturable in vitro remain diagnostically challenging, dependent historically on clinical findings, histology, or targeted molecular detection. We applied whole-genome sequencing directly from tissue to diagnose infections with mycobacteria (leprosy) and parasites (coenurosis). Direct pathogen DNA sequencing provides flexible solutions to diagnosis of difficult pathogens in diverse contexts.